THE PERCEIVED CHARACTERISTICS AND ADVANTAGES OF INFORMATION GAP ACTIVITIES IN LEARNING SPEAKING AT ENGLISHOPEDIA - Ana Resti Amalia (IAIN Syekh Nurjati Cirebon, 2019)
In EFL context the necessity of English, chiefly speaking skill is demanded when it comes as requirement for continuing higher education and facing cross-cultural communication. Information gap activity is considered to imply for developing students’ intelligence and ability to communicate and interact in real-situation. This research aims at explaining the implementation of information gap activities at Englishopedia and how students perceive the activities. The researcher used qualitative observational study, which the data were collected from observations, interview and documents. This research conducted in Englishopedia with 33 students during observation and 3 participants during interview were involved in this research. The research findings revealed that information gap activities facilitating the students in practicing speaking. The most prominent information gap activities were conversation through pair-work. Furthermore, the students were enthusiast in terms of pair-work activities, because it gave them new ideas, triggered to speak to other participants and enrollment of native speaker, thus establish students’ motivation to learn and using English.